Letter - Stolz, George
030-0099-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter Edition No. Paris, 6th August 1938. Mr. Ernest Bell, Trades Union Congress, Transport House, Smith Square, London, S.W.1 . Dear Comrade, In reply to your request received this morning, I would inform you that I have immediately given our printers an order for 1000 pamphlets regarding the relief action for Spain. These would have been sent immediately to you in London, but unfortunately the printers' office is closed to-day, so that they can only be sent on Monday. Yours sincerely, G. Stolz, Assistant Secretary. 292/946/30/99